IMPLEMENTASI E-GOVERNMENT DALAM MENINGKATKAN PELAYANAN DESA (DESA SUMBERSUKO KABUPATEN MALANG) - Nurchaerani Kadir; Nuzulul Huda; Eka Cahya Ningrum; Nanda Nafisah Puspiitasari (Department of Science and Technology Ibrahimy University, 2020)
The e-government system is one of the fundamental policies that can change the quality of public services from conventional to modern. The development of e-government is an effort to improve the quality of effective and efficient public services. E-government can be utilized to provide public services from the government to the public. The object of this research is Sumbersuko Village, located in Malang Regency, with the goal of being approved by e-government and then optimizing its use for government assistance in service and requests for public information. The e-government system is built on the Laravel framework, a website based on a MySQL database. With this e-Government, it is expected to be able to improve the quality of effective and efficient public services.